Impairment of cocaine-mediated behaviours in mice by clinically relevant Ras-ERK inhibitors - Papale, Alessandro; Spanagel, Rainer (eLife, 2016)
Ras-ERK signalling in the brain plays a central role in drug addiction. However, to date, no clinically relevant inhibitor of this cascade has been tested in experimental models of addiction, a necessary step toward clinical trials. We designed two new cell-penetrating peptides - RB1 and RB3 - that penetrate the brain and, in the micromolar range, inhibit phosphorylation of ERK, histone H3 and S6 ribosomal protein in striatal slices. Furthermore, a screening of small therapeutics currently in clinical trials for cancer therapy revealed PD325901 as a brain-penetrating drug that blocks ERK signalling in the nanomolar range. All three compounds have an inhibitory effect on cocaine-induced ERK activation and reward in mice. In particular, PD325901 persistently blocks cocaine-induced place preference and accelerates extinction following cocaine self-administration. Thus, clinically relevant, systemically administered drugs that attenuate Ras-ERK signalling in the brain may be valuable tools for the treatment of cocaine addiction.